Is It Only the Violence? : The Effects of Violent Video Game Content, Difficulty, and Competition on Aggressive Behavior - Hawk, Christopher E. and Ridge, Robert D. (Journal of Media Psychology, 2021)
Abstract. The results of prior research investigating whether the violence in violent video games leads to increased subsequent aggression are mixed. Some observers question whether the difficulty and/or the competitive aspects of these games are important, but overlooked, factors that also affect aggression. In the present study, participants ( N = 408) played a violent or nonviolent video game that was either difficult or easy and in which they competed and won, competed and lost, or did not compete against another player. Results revealed that participants became more aggressive only after playing a competitive, as opposed to a noncompetitive, game. Level of violence, winning or losing, and game difficulty did not have any significant effect. These results support the assertion that competition in video games has an independent and significant effect on subsequent aggression beyond violent content and game difficulty.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTAyNy8xODY0LTExMDUvYTAwMDI5MQ